Linguistic Manipulative Techniques in Advertising Slogans of Fast Food Restaurants - Dobzhanska-Knight, Nataliia; Добжанська-Найт, Найт; Voitko, Khrystyna; Войтко, Христина (My University, 2018)
The article deals with the notion of manipulation in advertising slogans of fast food restaurants. It focuses on techniques and means of language influence on the recipient. The article shows results of the study of 239 advertising slogans of fast food restaurants in English-speaking countries (a total number of 104 companies). Different language patterns which are used in advertising slogans and aimed at persuasion of customers on the subconscious level, are defined and analyzed; among them the most numerous are language patterns which create statements with distortions, deletions, and generalizations manifesting themselves in a variety of forms. The research also describes manipulative language patterns specifically related to advertising, such as unique selling proposition or life values. The authors also show quantitative proportions of the use of each pattern, as well as patterns used by the most successful and less successful restaurants. The most frequent of the manipulative language patterns are lost performatives, mind reading, and comparisons. The techniques of life values, mind reading, and antithesis are more common in advertising slogans of top restaurants compared to less popular ones. Individual slogans frequently manifest the use of more than one linguistic pattern of manipulation. У статті досліджено поняття маніпуляції в рекламних слоганах ресторанів фаст-фуду. Зосереджено увагу на засобах та методах мовного впливу на реципієнта. Праця показує результати дослідження 239 рекламних слоганів ресторанів фаст-фуду в англомовних країнах (всього 104 компанії). Розглянуто особливості мовних шаблонів, які часто використовуються для підсвідомого впливу на клієнтів, серед них найчисленнішими є лінгвальні засоби – твердження із впливом на підсвідомість, що містять викривлення, узагальнення та упущення, які виявляються у різноманітних формах. Дослідження також містить опис маніпулятивних мовних засобів, властивих рекламі: «унікальна торгова пропозиція» та «підлаштування під цінності». Автори також демонструють кількісні пропорції використання кожного засобу, а також порівнюють слогани популярних та менш популярних ресторанів швидкої їжі. Найхарактернішими є, зокрема, такі мовні засоби: втрачений перформатив, «читання думок» та порівняння. Прийоми «підлаштування під цінності», «читання думок» та антитеза характерніші для рекламних слоганів топ-ресторанів, у порівнянні з менш популярними компаніями. В одному слогані часто використано понад один лінгвальний засіб маніпуляції.
Лінгвістичні маніпулятивні засоби в рекламних слоганах ресторанів фаст-фуду
Keywords: manipulation; advertisement; metaphor; presupposition; generalization; deletion; distortion; маніпуляція; реклама; спотворення; упущення; узагальнення; пресупозиція; метафора